2020
DOI: 10.3390/biom10091278
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids in Embryonic Development

Abstract: Retinoids constitute a class of compounds chemically related to vitamin A [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A recent study shows that the p450 related drug metabolism pathways can regulate the replication of plant virus in insect ( 57 ). In vertebrates, retinoids play key roles in the process of embryonic development and tissue regeneration ( 58 , 59 ). Retinoid system is also harbored by invertebrates ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that the p450 related drug metabolism pathways can regulate the replication of plant virus in insect ( 57 ). In vertebrates, retinoids play key roles in the process of embryonic development and tissue regeneration ( 58 , 59 ). Retinoid system is also harbored by invertebrates ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of vitamin A on ASD still needs to be further clarified. The active metabolite of vitamin A is retinoic acid (RA), which activates retinoic acid receptors (RARs) and/or retinoid X receptors (RXRs) to regulate gene expression in many cells and tissues ( 33 , 34 ). In a mouse model, RA directly decreased inhibitory synaptic strength in the brain, resulting in excitation/inhibition imbalance ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In tunicates that have not secondarily lost the RAR gene, RAR-dependent RA signaling is implicated in neurogenesis as well as in tissue regeneration and bud development of budding tunicates [ 104 , 105 ]. The cephalochordate amphioxus is characterized by the most vertebrate-like RA signaling system of all invertebrates [ 99 , 106 ]. It has been demonstrated that the amphioxus RAR/RXR heterodimer can be activated by all- trans -RA, that HOX genes are directly regulated by RAR/RXR and that HOX-mediated RA signaling is essential for neurogenesis and axial patterning [ 107 ].…”
Section: Retinoic Acid Receptor (Rar)-dependent Signaling Is Requimentioning
confidence: 99%
“…It has recently been proposed that this repressive activity of RAR within the RAR/RXR heterodimer could be modified by RXR-dependent ligand binding [ 50 , 102 ]. It thus remains elusive how RA controls development and neurogenesis in mollusks [ 50 , 55 , 56 , 99 , 106 ]. Similarly, although the genomes of most ecdysozoans do not encode a RAR gene, there are indications for active roles of RA signaling in ecdysozoans, for example, during nervous system regeneration and in tissue repair of insects [ 108 , 109 ].…”
Section: Retinoic Acid Receptor (Rar)-dependent Signaling Is Requimentioning
confidence: 99%